A study of risk perception of radiofrequency electromagnetic field (RF-EMF) exposure from mobile phones and base stations in India. Issue 3 (3rd July 2022) - Pradhan, Rojalin; Rowley, Jack; Sagar, Mahim
ABSTRACT: Due to the ever-increasing use of mobile communications in India, health risks associated with exposure to radiofrequency electromagnetic field (RF-EMF) transmitted by mobile phones and base stations has become the focus of research. Internationally, there have been numerous studies on RF-EMF risk perception, but this issue is scarcely addressed in India. The present study evaluates the level of risk perception of Indians associated with RF-EMF exposure from mobile phones and base stations and assesses the underlying reasons for their concerns. We conducted a qualitative study on a small group of Indians ( n  = 25) from varied socioeconomic backgrounds, followed by a large-scale population ( n  = 500) survey to identify the primary issues of concern. The results show that many participants, irrespective of their social group, have a positive attitude towards mobile phones and are willing to accept the risks of using them, but are against the installation of base stations. Our study confirms that lack of knowledge about mobile communications technology, health concerns about mobile phones and base stations, community concern regarding base station deployment and media influence have a significant impact on risk perception among Indians. Carefully planned communication techniques are required to decrease risk perceptions and increase acceptance of mobile communications infrastructure.